A Systematic Review of Utilisation of Diurnal Timing Information in Clinical Trial Design for Long QT Syndrome - Seed, Lydia M.; Hearn, Timothy J. (Frontiers in Pharmacology, 2022)
Diurnal oscillations in human cardiac electrophysiology are thought to be under the control of the endogenous circadian clock. The incidence of arrhythmic events in patients with Long QT syndrome (LQTS) varies diurnally. The diurnal variation in QT interval has previously been identified as a potential for error in clinical trials which utilise ECG measurement. We performed a systematic review of clinical trials for LQTS to identify practice around specification of timing information for point electrocardiogram (ECG) measurements, analysis of continual ECG recordings ≥24 hours, and drug delivery. Despite guidelines having been issued around the analysis of 24-hour ECG recordings, we identify a lack of usage of detailed time of day information in trial design for LQTS studies, which has the potential to affect the interpretation of the results of drug trials. We identify that, in contrast, clinical trials for QT prolonging drugs demonstrate increased incorporation of time of day information of both QT analysis and drug dosing. We provide a visual portal to allow trial designers and clinicians to better understand timing of common cardiac-targeting drugs, and to bear this concept in mind in the design of future clinical trials.